Socio-demographic Factors Predicting Botho/Ubuntu in Online Education at an Open University Context - Magare, Ishmael; Trivedi, Shikha; Kasozi, Joseph Amooti (International Journal of E-Learning & Distance Education / Revue internationale de l’apprentissage en ligne et de l’enseignement à distance, 2025)
In this study, we investigated the impact of socio-demographic factors on the manifestation of Botho/Ubuntu philosophy in online education. We used Albert Bandura's Social Cognitive Theory to understand how Botho influences stakeholders' attitudes and actions. We employed a quantitative approach with a cross-sectional design and gathered data through a survey. The respondents in the study included staff, tutors, and students associated with an open university. We conveniently selected a sample of 263 respondents from the open university’s five regional campuses and headquarters. The findings indicated that age, marital status, and tenure with the university significantly influenced stakeholders' perceptions of Botho principles in online teaching and learning. This study highlights the importance of incorporating Botho/Ubuntu principles in online education to establish inclusive and supportive virtual learning environments. Educators can use these findings to foster student engagement and success. However, further research is necessary to comprehensively understand the effect of Botho/Ubuntu principles on student outcomes and explore stakeholders' perspectives on their effectiveness.